Effects of fermentation with different microbial species on the umami taste of Shiitake mushroom (Lentinus edodes). (April 2021) - Chen, Ziqi; Gao, Haiyan; Wu, Weijie; Chen, Hangjun; Fang, Xiangjun; Han, Yanchao; Mu, Honglei
Abstract: To explore the effects of fermentation on the umami taste substances of shiitake mushrooms ( Lentinus edodes ), the umami substances of fermented shiitake mushrooms using different microorganism species were investigated. Saccharomyces cerevisiae, Aspergillus oryzae, Aspergillus niger and Lactobacillus plantarum were selected to ferment the pileus and stipe of shiitake mushrooms, and the umami substances in the fermentation liquid were analyzed and compared. The contents of free amino acids and flavor nucleotides were measured, and the taste activity value (TAV) and equivalent umami concentration (EUC) were calculated to evaluate the taste of fermentation. The results showed that acidity as well as the content of free amino acids and flavor nucleotides in the fermentation broth increased throughout the fermentation process. The EUC values of the fermentation broths ranged from 9.95 to 34.58 g monosodium glutamate (MSG)/100 g, and TAVs were greater than 1. According to our analysis, Lactobacillus plantarum was the best species for fermentation providing the strongest umami flavor. Highlights: Umami of shiitake mushrooms can be significantly enhanced by fermentation. Pileus and stipe fermentation with four different species were compared. Acidity, free amino acids and flavor nucleotides were increased by fermentation. Overall umami flavor was mostly enhanced by Lactobacillus plantarum .